Integrating science for simultaneously addressing loss and damage from climate change and strengthening social protection - Desai, Bina; Läderach, Peter; Roy, Shalini; Meddings, George; Costella, Cecilia; Bidault, Nicolas; Solórzano, Ana; Campbell, Raramai (Frontiers in Climate, 2025)
Expanding social protection to at-risk communities in climate-vulnerable countries is proposed to become a core pillar of addressing loss and damage associated with climate change. Conceptual advances have been made but remain disconnected from realities: expanding the currently low coverage of social protection in climate-vulnerable countries will require significant additional resources, including from the newly set up Fund for Loss and Damage. Moreover, the evidence base for resource allocation and programme delivery will have to become significantly stronger, and the required integrated science approaches and corresponding assessment tools are yet to be developed.